STRATEGI KOMUNIKASI PARIWISATA PEMERINTAH KABUPATEN ACEH SELATAN DALAM MERAIH PREDIKAT DESTINASI KREATIF PADA OBJEK WISATA PULAU DUA TAHUN 2022 - Al Furqan, M Imam; Ritonga, Dedi Prima (Jurnal Psikotes, 2024)
Maritime tourism is one of the tours that is in great demand by tourists at this time, in addition to the beauty of the sea and the beach, the existence of a small island is also very attractive, including one of them, South Aceh's island tour which won the victory in the Anugerah Pesona Indonesia 2022 event. The purpose of this research is to explain the tourism communication strategy of the South Aceh Government in achieving the Indonesian Charm Award in 2022. This research uses qualitative research methods. The data obtained in this study used data collection techniques from various sources, namely observation, interviews, and documentation that has been written in field notes and then documented personally through pictures and photos. The stages in the data analysis process are data selection, data reduction, data presentation, and conclusion drawing. The results obtained from this study are that the South Aceh government greatly utilizes the existence of social media in this achievement and certainly cannot be separated from good tourism communication management. It was found that the tourism communication strategy used by the South Aceh Government could not be separated from the studies in tourism communication.